Fabrication of chelate‐setting α‐tricalcium phosphate cement using sodium citrate and sodium alginate as mixing solution and its in vivo osteoconductivity. Issue 6 (17th November 2017) - Konishi, Toshiisa; Lim, Poon Nian; Honda, Michiyo; Nagaya, Masaki; Nagashima, Hiroshi; Thian, Eng San; Aizawa, Mamoru
Abstract: Moldable and injectable calcium‐phosphate cements (CPCs) are material candidates for bone replacement applications. In the present study, we examined the effectiveness of sodium alginate and sodium citrate additives to the liquid phase of CPC, in improving its handling property as well as mechanical strength. The use of these additives enhanced the handling property significantly, in terms of consistency as compared to CPC without additives due to the liquefying effect caused by the adsorption of citrate ions on the cement particles. Sodium alginate and sodium citrate were added to CPC, which was set by the chelate‐bonding capability of inositol phosphate, and was composed of mainly α‐tricalcium phosphate (α‐TCP) phase (>90%). The compressive strength of the CPC containing sodium alginate and sodium citrate was 3.4 ± 0.3 MPa, which was significantly higher than cement without additives. Furthermore, this cement exhibited favorable osteoconductivity and bioresorbability, and remained the α‐TCP phase after 4‐week implantation in a pig tibiae model. These results suggested that the cement is a potential candidate as a bioresorbable paste‐like artificial bone. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2361–2370, 2018.